OPTIMALISASI TINGKAT PEMANFAATAN FASILITAS DASAR DAN FUNGSIONAL DI PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN JAKARTA DALAM MENUNJANG KEGIATAN PENANGKAPAN IKAN - Sinaga, Genesis Vennikson; Rosyid, Abdul; Wibowo, Bambang Argo (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Nizam Zachman Ocean Fishery Port Jakarta (PPSNZJ) is the center of fishing activities in Jakarta. This is supported by the location of its strategic location that has the potential to own a good fhishery resources. As Indonesia entered the ara of decentralization, each district is required to be able to support their own region to optimize the full potential of the area both real and non real sector. Therefore, in the fisheries sector, built Nizam Zachman Jakarta Ocean Fishery Port (PPSNZJ). The study aims to determinate the condition of facilities, to analyze the level of optimization, and analyze appropriate strategies to be applied in the development of PPSNZJ with current condition. The method used in this study was descriptive sampling and purposive sampling analysis of the utilization rate of facilities and SWOT analysis were used in this study. The result obtained that the existing facilities at the Nizam Zachman Jakarta Ocean Fishery Port (PPSNZJ) was still good condition and still proper to use, with the cruise line utilization rate 87%, 96% harbor pool, pier 110%, 129% TPI. From these result could be concluded than the optimization of basic facilities and fully functional facilities have not been utilized optimally. While the result obtained from the application of SWOT analysis S-O strategy (Strength-Opportunity) which means that the strategy in its application to use force to take advantage of an opportunity.